Analisis Faktor-Faktor yang Mempengaruhi Audit Going Concern Pada Perusahaan Manufaktur Periode 2018-2020 - Tanadi, Wilsen; Iskak, Jamaludin (Jurnal Paradigma Akuntansi, 2023)
This research was conducted to examine the effect of audit quality, liquidity, profitability, growth, firm size, and previous year's audit opinion on the formation of going concern audit opinions on manufacturing sector that listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. The sample was selected by purposive sampling method and the valid data were 32 companies. The data processing technique uses logistic regression analysis supported by SPSS software (Statistical Product and Service Solution) 25 program for Windows and Microsoft Excel 2019. The results show that audit quality, liquidity, profitability, growth and firm size have no effect on the formation of a going audit opinion. concern. While, the previous years audit opinion had a positive effect on the formation of a going-concern audit opinion.